PELATIHAN KEWIRAUSAHAAN DENGAN MEMBUATNUGGED SEHAT - Yulianto Yulianto (Asian Journal of Innovation and Entrepreneurship, 2015)
The entrepreneurship training program is aims to open the potential of humanresources of Dusun Klakah Nduwur, especially the community of mothers. The benefitsof this training program is the community of mothers in Dusun Klakah Nduwur canspend their spare time in the dry season by creating product that has a sale value,because cintrong (crassocephalum crepidioides leaves) chips that produced by them canbe produced only in rainy season, because the leaves grown in the rainy season only.The method that used in this training program is practicing in making healthy nuggeddirectly together with the mothers. This training program is conducted in one of themothers’ house. The results of this program is the mothers have a new product that hasa sale value and can be marketed and become the family income and also the potentialfrom the community also began to open to bold innovation in entrepreneurship.